Along for the ride a novel - Dessen, Sarah (New York Viking, 2009)
When Auden impulsively goes to stay with her father, stepmother, and new baby sister the summer before she starts college, all the trauma of her parents' divorce is revived, even as she is making new friends and having new experiences such as learning to ride a bike and dating
1
Keywords: Babies -- Fiction; Change -- Fiction; Dating (Social customs) -- Fiction; Divorce -- Fiction; Interpersonal relations -- Fiction; Stepfamilies -- Fiction